Critique of enhanced power claimed for Quasi-ANCOVA and Dual-Centered ANCOVA - B. Wade Brorsen; Hua Lin; Robert E. Larzelere (PLoS ONE, 2025)
Two related methods, Quasi-ANCOVA and Dual-Centered ANCOVA, have recently been suggested as a way to get greater power when analyzing data from a before and after study. Both methods use group-mean centering where the groups are the treatment and comparison groups. Group-mean centering creates a generated regressor problem. When the estimated standard errors are corrected for the generated regressor problem, there is no longer any gain in power. The corrected Quasi-ANCOVA estimates are identical to those from ANOVA and the corrected Dual-Centered ANCOVA estimates are identical to those from the differences model. These conclusions are derived analytically and also verified using a Monte Carlo simulation.